Assemblage thinking and actor‐network theory: conjunctions, disjunctions, cross‐fertilisations. Issue 3 (15th March 2016) - Müller, Martin; Schurr, Carolin
Abstract : This paper shows that assemblage thinking and actor‐network theory (ANT) have much more to gain from each other than debate has so far conceded. Exploring the conjunctions and disjunctions between the two approaches, it proposes three cross‐fertilisations that have implications for understanding three key processes in our socio‐material world: stabilisation, change and affect. First, the conceptual vocabulary of ANT can enrich assemblage thinking with an explicitly spatial account of the ways in which assemblages are drawn together, reach across space and are stabilised. Second, each approach is better attuned to conceptualising a particular kind of change in socio‐material relations: ANT describes change without rupture, or fluidity, whereas assemblage thinking describes change with rupture, or events. Third and last, assemblage thinking could fashion ANT with a greater sensitivity for the productive role of affect in bringing socio‐material relations into being through the production of desire/wish ( désir ). We demonstrate the implications of these cross‐fertilisations for empirical work through a case study of the global market for assisted reproduction.